Autosomal rearrangement in Gryllus assimilis Fabricius, 1775 (Orthoptera, Gryllidae) - Zefa, Edison [UNESP] (Sociedade Brasileira de Genética, 1999)
A espécie Gryllus assimilis L. apresenta 2n = 29, X0 (macho) e 2n = 30, XX (fêmea), porém em alguns indivíduos coletados na cidade de Rio Claro, São Paulo, Brasil, foram encontrados dois cariótipos distintos: o cariótipo básico e outro rearranjado, com 2n = 28, X0 e 2n = 29, XX. O rearranjo foi interpretado como sendo autossômico e heterozigoto, caracterizado pela translocação envolvendo dois pares de homólogos submetacêntricos: o par 10, que possivelmente tem um dos elementos com uma inversão pericêntrica, e o par 6, que possui em seu braço curto duas constrições secundárias, diferenciando satélites em suas extremidades.

Gryllus assimilis L. has a karyotype of 2n = 29 (X0, male) and 30 (XX, female). The above karyotype was encountered along with another in which 2n = 28 (X0, male) and 2n = 29 (XX, female) in a population from the outskirts of Rio Claro city (São Paulo State, Brazil). of eight specimens studied, five had the heterozygous karyotype involving a translocation and three had the basic karyotype. There were no individuals homozygous for the rearrangement. The heterozygous karyotype was the result of a chromosomal rearrangement between chromosome pairs 6 and 10, both of which were initially submetacentric. The members of the sixth pair normally have two constrictions in the small arm, with a satellite at the chromosome tip. The chromosome of the tenth pair involved in the translocation was generally submetacentric and probably underwent a pericentric inversion which transported the centromere to a subterminal position before being translocated. In this case, the long arm of the inverted chromosome of the tenth pair was translocated with the satellite of a member of the sixth pair.